Magnetite compensates for the lack of a pilin-associated c-type cytochrome in extracellular electron exchange - Liu, Fanghua; Rotaru, Amelia-Elena; Shrestha, Pravin M.; Malvankar, Nikhil S.; Nevin, Kelly P.; Lovley, Derek R. (Environmental microbiology, 2015)
Summary Nanoscale magnetite can facilitate microbial extracellular electron transfer that plays an important role in biogeochemical cycles, bioremediation and several bioenergy strategies, but the mechanisms for the stimulation of extracellular electron transfer are poorly understood. Further investigation revealed that magnetite attached to the electrically conductive pili of Geobacter species in a manner reminiscent of the association of the multi‐heme c‐type cytochrome OmcS with the pili of Geobacter sulfurreducens. Magnetite conferred extracellular electron capabilities on an OmcS‐deficient strain unable to participate in interspecies electron transfer or Fe(III) oxide reduction. In the presence of magnetite wild‐type cells repressed expression of the OmcS gene, suggesting that cells might need to produce less OmcS when magnetite was available. The finding that magnetite can compensate for the lack of the electron transfer functions of a multi‐heme c‐type cytochrome has implications not only for the function of modern microbes, but also for the early evolution of microbial electron transport mechanisms.